Benefits of using dry needling for the treatment of pain in patients with headaches. Systematic review - Rubén Martínez, Hugo; Martinez, Cesar (International Journal of Neurology, 2024)
The aim of this study was to evaluate the effectiveness of dry needling in reducing the intensity and frequency of pain in patients with headaches, especially chronic tension headaches and cervicogenic headaches. To this end, a systematic review was conducted based on an exhaustive search of the PubMed, Scielo, and Google Scholar databases, using Boolean operators and MeSH terms related to headaches and dry needling. Of a total of 475 articles identified, three studies that met the previously established inclusion criteria were selected. The total sample consisted of 371 patients, of both sexes and over 12 years of age, diagnosed with chronic headaches. The included studies were randomised clinical trials comparing dry needling with sham needling, conventional physiotherapy, therapeutic exercises and combinations with spinal manipulation. The main variables analysed were headache intensity and frequency, measured using validated scales such as the visual analogue scale, headache diaries and disability indices. The results consistently showed that dry needling produced significant and clinically relevant reductions in both headache intensity and frequency compared to the control groups. Improvements were also observed in associated disability, cervical function, and patients' quality of life. These effects were maintained in the short- and medium-term follow-ups. In conclusion, the evidence analysed supported the efficacy of dry needling as an effective therapeutic intervention within the kinesiological approach to chronic headaches, highlighting its potential to comprehensively improve the condition and quality of life of patients.